Promoting Human-Computer Interaction Values and Practices in Small and Emerging Economies - Zaphiris, Panayiotis; Lamas, David; Christou, Georgios (My University, 2013)
This special interest group aims to further the understanding of the challenges related to the design and evaluation of digital interactive artifacts in small and emerging economies. Computing is at one of its most exciting moments, playing an essential role in supporting human activities, facilitated by the growing availability of services, devices and interaction modalities. Moreover, with the evolution from the large-scale computing to the contemporary ubiquitous computing, users were brought from the periphery to the center of an emerging pervasive socio-technical system, which pulled the inherent interaction paradigms through the successive waves of the personal, networked, collaborative, mobile, augmented and virtual reality interaction paradigms. Notwithstanding, in many small and emerging economies, interactive systems are still being designed and evaluated without fully taking into account our cognitive abilities, giving little or no consideration to the ways we perceive and handle information, go about our work and life, create and maintain social relations, and use our cultural context and relate to our environment, thus failing to realized the technology’s potential.
Keywords: Human computer interaction; Emerging economies